2019
DOI: 10.1021/jacs.9b08832
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Cycloalkanes from Diols and Secondary Alcohols or Ketones Using a Homogeneous Manganese Catalyst

Abstract: A method for the synthesis of substituted cycloalkanes was developed using diols and secondary alcohols or ketones via a cascade hydrogen borrowing sequence. A non-noble and air-stable manganese catalyst (2 mol %) was used to perform this transformation. Various substituted 1,5-pentanediols (3–4 equiv) and substituted secondary alcohols (1 equiv) were investigated to prepare a collection of substituted cyclohexanes in a diastereoselective fashion. Similarly, cyclopentane, cyclohexane, and cycloheptane rings we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(37 citation statements)
references
References 65 publications
0
37
0
Order By: Relevance
“…The anticipated trifluoroalkylated bis‐indole product 3 aa was formed in 10 % yield. Inspired by the recent advances of first‐row transition metal catalysts in AD processes, [12f–j] we tested various metal catalysts in combination with different bases. Co(acac) 2 with Cs 2 CO 3 furnished the expected compound 3 aa in 40 % isolated yield (Table 1, entry 3).…”
Section: Figurementioning
confidence: 99%
“…The anticipated trifluoroalkylated bis‐indole product 3 aa was formed in 10 % yield. Inspired by the recent advances of first‐row transition metal catalysts in AD processes, [12f–j] we tested various metal catalysts in combination with different bases. Co(acac) 2 with Cs 2 CO 3 furnished the expected compound 3 aa in 40 % isolated yield (Table 1, entry 3).…”
Section: Figurementioning
confidence: 99%
“…Next, intramolecular reactions were attempted (Figure 6). A diol as an alkylation precursor was used in iridium and manganese‐catalyzed cross‐coupling of ketones ( sec ‐alcohols) and diols [35,55,56] . In this study, the intramolecular cyclizations of diols in the absence of enolate precursors were conducted.…”
Section: Resultsmentioning
confidence: 99%
“…Various homogeneous transition‐metal catalysts have been reported for transition metal‐catalyzed β‐alkylation of alcohols via the BH strategy. Iridium, ruthenium, palladium, iron, copper, manganese, cobalt, and nickel catalysts were employed for cross‐coupling of secondary and primary alcohols [6–37] . For the condensation of primary alcohols (Guerbet reaction), iridium, rhodium, ruthenium, and manganese catalysts were employed [5,38–49] .…”
Section: Introductionmentioning
confidence: 99%
“…Donohoe and co-workers have shown that pentamethylphenyl( Ph*) ketones can be alkylated with aw ide varietyo f primary or secondary alcohols and diols. [52,53] The Ph* group is pivotalf or these transformations-because the aryl group is orthogonal to the carbonyl, the ortho-methyl groups protect it from undesired reduction and homodimerization processes. Moreover,t he Ph* group can readily be converted to aw ide range of functional groups (e.g.,e sters, amines, acidsa nd alcohols) by retro-Friedel-Crafts acylation.…”
Section: Selectiveenone Reductionmentioning
confidence: 99%